Necrose da mucosa esofágica como complicação da cardiomiotomia à heller para tratamento de megaesôfago chagásico - Aires,Nádia Barbosa (2002)
This article presents a complication of the laparoscopic technique for Heller cardiomyotomy and anterior fundoplication. This procedure is safe and provides excellent relief of disphagia in esophageal achalasia. Nevertheless, there are rare but dangerous complications, such as late active digestive bleeding, presented in this paper which was resistant to conservative treatment and led to hypovolemic shock. Urgent laparotomy performed to identify and control bleeding, revealed necrosis of esophageal mucosa with a bleeding gastric vessel. Inadequate exposure of the gastroesophageal junction and an incision very close to the lesser curvature might have damaged the esophageal branches of the left gastric artery, leading to ischemic necrosis of the mucosa and exposure of the gastric wall and its vessels.